Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES - ESPELTA, J M; RETANA, J; Gené, C; Riba, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:
Keywords: Aleppo pine; Holm oak; mixed forest; Seedling; survival curve